2007
DOI: 10.1364/josaa.24.001793
|View full text |Cite
|
Sign up to set email alerts
|

Sharper focal spot formed by higher-order radially polarized laser beams

Abstract: The intensity distributions near the focal point for radially polarized laser beams including higher-order transverse modes are calculated based on vector diffraction theory. For higher-order radially polarized mode beams as well as a fundamental mode (R-TEM01*) beam, the strong longitudinal component forms a sharper spot at the focal point under a high-NA focusing condition. In particular, double-ring-shaped radially polarized mode (R-TEM11*) beams can effectively reduce the focal spot size because of destruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(82 citation statements)
references
References 19 publications
1
80
0
1
Order By: Relevance
“…It is entirely conceivable that even more complex waveguide geometries could lead to much higher mode stability, or the ability to generate and propagate even more complex vortex beams that are theoretically postulated [56] to facilitate spots as small as 0.14λ 2 .…”
Section: Mode-division Multiplexingmentioning
confidence: 99%
“…It is entirely conceivable that even more complex waveguide geometries could lead to much higher mode stability, or the ability to generate and propagate even more complex vortex beams that are theoretically postulated [56] to facilitate spots as small as 0.14λ 2 .…”
Section: Mode-division Multiplexingmentioning
confidence: 99%
“…Nowadays, highly focused beams are present in numerous research areas and technical applications [1][2][3][4][5][6][7][8][9][10]. However, to the best of our knowledge no research has been reported in the field of optical security [11][12][13], using focused fields.…”
Section: Introductionmentioning
confidence: 99%
“…The propagation of electromagnetic field distributions generated at the focal region has been extensively investigated in the last years [1][2][3][4][5][6][7][8]. Non-paraxial fields have demonstrated very useful in many fields for instance in high-resolution microscopy, particle trapping, high-density recording, tomography, electron acceleration, nonlinear optics, and optical tweezers [9].…”
Section: Introductionmentioning
confidence: 99%